2008
DOI: 10.1111/j.1365-2923.2008.03113.x
|View full text |Cite
|
Sign up to set email alerts
|

Is it me or is it them? Factors that influence the passing of underperforming students

Abstract: Many different factors impact on medical educators' failure to report underperformance in students. There are conflicts between these factors and the need to report competence accurately (i.e. duty to protect the public). Although some of the barriers identified are similar to those found in previous studies, using a theory-based approach added value in that it facilitated a richer exploration of failure to fail. Insights offered in this study will be used to plan a questionnaire study and subsequent intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
175
1
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(214 citation statements)
references
References 19 publications
14
175
1
24
Order By: Relevance
“…The value placed on this global assessment cannot be underestimated. Personal uneasiness on failing a candidate has been noted before 14 and it was again noted in discussion as well as the evaluation, highlighting that assessors were very prepared to use the full range of grade marks wherever possible.…”
Section: Discussionmentioning
confidence: 90%
“…The value placed on this global assessment cannot be underestimated. Personal uneasiness on failing a candidate has been noted before 14 and it was again noted in discussion as well as the evaluation, highlighting that assessors were very prepared to use the full range of grade marks wherever possible.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore the Audétat et al study suggested that supervisors' beliefs might be better represented as viewpoints. 13 Q methodology was developed by Stephenson to explore shared viewpoints. 20,21 Participants are asked to rank (sort) a precompiled list of statements based on their level of agreement.…”
Section: Beliefs Regarding Supervisionmentioning
confidence: 99%
“…excessive loss of confidence) which conflicted with their need to be supportive as part of a caring culture. 14 Supervisors in Audétat et al's study 13 believed that good residents would simply pick-up skills through being immersed in the clinical setting and observing clinicians, thus implying that they could fulfil both their clinical duties and their educational ones through their clinical work. These examples illustrate the potential links between beliefs and identities, both individual (being a clinical teacher as being intertwined with being a clinician) and social (being lenient as being indicative of belonging to a caring culture).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations